Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3109/09553002.2013.782449
|View full text |Cite
|
Sign up to set email alerts
|

Brain hsp70 expression and DNA damage in mice exposed to extremely low frequency magnetic fields: A dose-response study

Abstract: These data show that high density ELF-MF only induce reversible brain DNA damage while they do not affect hsp70 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The expression on hsp70 mRNA in the brain tissues of CD1 mice exposed to 50 magnetic fields was investigated by Villarini et al (2013). Animals were exposed to 0.1, 0.2, 1 or 2 mT for 15h/day for 7 days using a pair of rectangular coils in a Helmholtz-like configuration.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…The expression on hsp70 mRNA in the brain tissues of CD1 mice exposed to 50 magnetic fields was investigated by Villarini et al (2013). Animals were exposed to 0.1, 0.2, 1 or 2 mT for 15h/day for 7 days using a pair of rectangular coils in a Helmholtz-like configuration.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…According to recent literature, ELF‐MF exposure is believed to play a role in the later stages (promotion and progression) of tumorigenesis, especially in brain‐derived tumors (Poulletier de Gannes et al, ; Turner et al, ). Critical cellular pathways and functions have been proposed as targets of ELF magnetic fields: DNA damage profile (Panagopoulos et al, ; Villarini et al, ; Yoon et al, ), proliferation and/or survival dynamics (Martínez et al, ; Trillo et al, ; Razavi et al, ), signaling pathways (Nie and Henderson, ; Patruno et al, ), and redox balance (Falone et al, ; Falone et al, ; Di Loreto et al, ; Mattsson and Simkó, ). We have previously shown that the exposure to an ELF magnetic field increases the proliferation of cells isolated from neuroblastoma, and this was linked to the novel expression of protein associated to a more malignant phenotype (Sulpizio et al, ).…”
mentioning
confidence: 99%
“…Whether ELF-MFs are able to induce hsp70 expression still remains a controversial issue. For example, hsp70 has been found to increase after ELF-MF exposure (Tokalov and Gutzeit, 2004; George et al, 2008; Blank and Goodman, 2009), while others reported negative results (Mariucci et al, 2010; Villarini et al, 2017, 2013). Because the experimental conditions were different from each other in regard to equipment used to generate MFs, exposure protocol (frequency, flux intensity and/or time) and biological material (cell lines and animal species, strain and age), the results of various studies may be different.…”
Section: Discussionmentioning
confidence: 98%